2013
DOI: 10.1163/15685381-00002918
|View full text |Cite
|
Sign up to set email alerts
|

Iris photo-identification: A new methodology for the individual recognition of Tarentola geckos

Abstract: Gekkonid field studies are hampered by the difficulty to individually recognize individuals. In this study we assess the feasibility of using their variegated iris pattern to photo-identify Tarentola boettgeri bischoffi, a threatened Macaronesian endemic. Using a library of 924 photos taken over a 9-month period we also evaluate the use of the pattern matching software Interactive Individual Identification System (I3S) to match photos of known specimens. Individuals were clearly recognized by their iris patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…However, even in these conditions, parallax effects of taking photographs at wide horizontal angles (>30°) to the subject can still be problematic for the automated matching process (Speed et al 2007;Hartog and Reijns 2014). The greater the horizontal angle of deviation from 0°(perpendicular to the subject), the higher the likelihood of a low scoring match (Speed et al 2007;Rocha et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in these conditions, parallax effects of taking photographs at wide horizontal angles (>30°) to the subject can still be problematic for the automated matching process (Speed et al 2007;Hartog and Reijns 2014). The greater the horizontal angle of deviation from 0°(perpendicular to the subject), the higher the likelihood of a low scoring match (Speed et al 2007;Rocha et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For smaller taxa (<500 g), parallax effects are likely to be exacerbated because of the comparatively small body areas being photographed. Most studies of smaller-sized fauna have controlled for the parallax problem by capturing the animal and manipulating it into a fixed position relative to the camera, photographing either in-hand or using a holding pen (Bradfield 2004;Frisch and Hobbs 2007;Sacchi et al 2007;Hachtel et al 2009;Kenyon et al 2009;Knox et al 2013;Rocha et al 2013;Drechsler et al 2015). This reintroduces the potential stress that the noninvasive technique is supposed to avoid, and involves a large effort to capture the animal for photography.…”
Section: Introductionmentioning
confidence: 99%
“…However, we urge that all necessary precautions must be taken to increase picture quality and reduce misidentification of individuals. The use of automatic recognition using standardised scoring softwares may speed up identification (Speed et al 2007;Rocha et al 2013;Bradley and Eason 2018), but its applicability on Hydromantes still needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, photographic recognition also has some limitations. First, this method only works well for species that have a defined pattern but its application is challenging in species having uniform colouration (Carafa and Biondi 2004;Martin-Smith 2011;Rocha et al 2013;Carpentier et al 2016). In addition, it does not allow monitoring the development of young individuals into adults in species where the pattern changes during ontogenesis (Lanza et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The I 3 S program has been shown to match images successfully 95% (Rocha et al, 2013) and 83% (Speed et al, 2007) of the time as compared to images matched by-eye, and Rocha et al (2013) found this method to be significantly faster than by visual comparison. These studies controlled for postural positioning and other effects, such as glare, flight behavior, and availability of body surface, which increases the success of I 3 S.…”
Section: S-s-a Critical Assumption When Using Pattern-recognitionmentioning
confidence: 99%